Image Quality and Information Parameters of Electronic Portal Imaging Devices - Marios K. Tzomakas; Vasiliki Peppa; Antigoni Alexiou; Georgios Karakatsanis; Anastasios Episkopakis; Christos Michail; Ioannis Valais; George Fountos; Nektarios Kalyvas; Ioannis S. Kandarakis (Applied Sciences)
In this study, the imaging performance of electronic portal imaging devices (EPIDs) is evaluated, comparing measurements collected from EPID images captured at 115 cm, with a field size of 15 × 15 cm2, monitor units (MUs) in the range of 2 MU-100 MU and dose rates (DRs) of 200 MU/min, 400 MU/min and 600 MU/min, using a 6 MV LINAC system and the QC-3V image quality phantom. The analysis includes the normalized contrast transfer function (CTFnorm), the noise power spectrum (NPS) and the information capacity (IC), as well as the signal-to-noise frequency response (SNFR), which can be used as a comprehensive quality index. The results of our study are compared with previously published data captured at 100 cm under similar exposure conditions. They show similar CTF curves with different source-to-phantom distances, with the lowest values observed at specific MU and DR combinations. Moreover, NPS graphs are found to decrease with respect to spatial frequency. SNFR values also display a reduction with increasing spatial frequency. In addition, irradiation with the phantom placed closer to the EPID, 115 cm from the LINAC, yields better SNFR and IC performance characteristics, indicating better delineation of the organs closer to the EPID. The testing of EPID performance may potentially benefit from our results, which may lead to improvements in the quality of radiotherapy treatments.